Removal of filling material in endodontic retreatment: a literature review - Carina do Nascimento Menezes; Verydianna Frota Carneiro; Mônica Sampaio do Vale (Revista Sul-Brasileira de Odontologia, 2019)
Removal of filling material from the root canal system is required when a previous endodontic treatment fails, what may result in the permanence of an unfavorable periapical condition. The intent is to completely remove the filling material from the root canal to achieve sufficient cleaning and shaping for successful retreatment. Objective: The aims of this article were to provide a systematic review of the different techniques of endodontic filling material associated or not with organic solvents and to analyze them critically in terms of advantages and disadvantages of each technique. Literature review: The descriptors used were “gutta-percha”, “obturation,” and “retreatment” in the following databases: PubMed, MEDLINE, Latin American and Caribbean Center on Health Sciences Information (Bireme), Latin-American and Caribbean Health Sciences (Lilacs), Brazilian Dentistry Bibliography (BBO), and Scientific Electronic Library Online (SciELO). Publications of in vitro/ex vivo and in vivo experiments without language restriction between the years 2010 and 2018 were selected. Conclusion: None of the techniques were capable of performing complete root canal cleaning, and the manual method was so effective as the automated method, although it requires longer working time. Furthermore, although this review confirmed that the solvent action did not allow a significant improvement in the removal of the filling material, ultrasound-activated irrigation proved to be an efficient adjunctive device as it could significantly reduce the volume of intracanal residuals.